Characterization Of Groundwater Facies Using The Piper Diagram In The Rakihan Lake Area, Sindang Danau District, South Ogan Komering Ulu Regency, South Sumatra Province - Dianita Septia Wardani; Budhi Setiawan; Dede Nurohim (Jurnal Ilmiah Dinamika Rekayasa, 2026)
Lake Rakihan is a water system located in the active zone of the Sumatran Fault that developed in a volcanic environment; as a result, its hydrogeochemical characteristics are influenced by local geological conditions. This study aims to identify the hydrogeochemical characteristics of groundwater and surface water in the Lake Rakihan area, South Ogan Komering Ulu Regency, South Sumatra, based on water chemistry analysis. The concentrations of major ions were converted to milliequivalents per liter (meq/L) and validated using the Charge Balance Error (CBE) method before being interpreted using a Piper diagram. The validation results showed that only samples C473-4, C473-5, and C473-6 met the ion balance criteria (CBE ≤ ±5%), while the other samples did not meet the criteria and were therefore not used in the interpretation. The Piper diagram indicates that samples C473-4 and C473-6 belong to the Ca–Mg–HCO₃ facies, while C473-5 falls within the Mixed Type facies between Mg–HCO₃ and Ca–Cl. The dominance of Ca²⁺, Mg²⁺, and HCO₃⁻ ions indicates that the hydrogeochemistry of the water is primarily controlled by water–rock interaction processes through the weathering of volcanic rocks. In general, the hydrogeochemical system in the Lake Rakihan area reflects the characteristics of local groundwater flow, which is still dominated by natural processes.